Integration of Cost Sensitivity Analysis and Transportation Optimization: A Bibliometric Approach and Implications - Meliniarta Nadhiva; Muftiadi, R. Anang; Arifianti, Ria (JURNAL MANAJEMEN MOTIVASI, 2026)
This study explores the integration of cost sensitivity analysis and transportation optimization through a Systematic Mapping Study (SMS) using Scopus data from 2019 to 2023. Bibliometric analysis and VOSviewer visualization identified publication trends, research methods, and thematic clusters. Results show China as the largest contributor and highlight six key clusters including sensitivity analysis, uncertainty, optimization algorithms, and sustainable logistics. A significant research gap exists in combining cost sensitivity with holistic sustainability models. The findings offer academic and practical implications to guide future research and policy formulation in building more adaptive, efficient, and resilient transportation and distribution systems amid cost uncertainty.